Design Details and Long-term Performance of VIPs in Canada's North. (March 2017) - MacLean, Doug; Mukhopadhyaya, Phalguni; Korn, Juergen; Mooney, Stephen
Abstract: Vacuum Insulation Panels (VIPs) have been used in a variety of insulation applications in the built-environment in Yukon, Canada, which is located North of 60° latitude. As a result of this experience in a cold climate, more information is now available about the long-term thermal performance of VIPs and the best ways to install them. This paper compiles updated design, field and monitoring information from our experience for researchers, designers, building owners and contractors to help accelerate the use of high-performance VIPs with the goal of achieving Near Net Zero energy-use in buildings in the most cost-effective way.